Variability of water exchanges through the Strait of Hormuz - Vasou, Panagiotis; Vervatis, Vassilios; Krokos, George; Hoteit, Ibrahim; Sofianos, Sarantis (2020)
The variability of the water mass exchange between the Arabian Gulf and the Indian Ocean is investigated using a high-resolution (1/36°) ocean model. We focus on the period from December 1996 to March 1998, having as reference in situ measurements at the Strait of Hormuz. Previous studies, based on models and observations, suggested a perpetual deep outflow, mainly in the southern part of the Strait, and a variable flow in the upper layers. In the present study, we confirm that there is a permanent core of a deep outflow in the Strait at depths greater than 40 m, characterised by high-salinity waters. In addition, we show that there is a seasonal signal in the upper layers net flow in the southern part of the Strait, altering from net inflow during winter/spring to net outflow during summer/fall. The mean annual inflow through the Strait is estimated at 0.22 ± 0.01 Sv and the deep outflow at 0.147 ± 0.01 Sv. The water mass exchange through the Strait is controlled by synoptic processes with high variability net transport fields. These processes characterise the structure and the intensity of the transport patterns, exhibiting 2- to 5-day period. On synoptic time scales, winds drive an immediate baroclinic flow at the Strait of Hormuz, affecting mostly the upper layers, and a quasi-barotropic flow that peaks approximately 2 days later.